Gamification Techniques in Teaching and Learning Exploratory Courses in Technology and Livelihood Education: A Phenomenological Study - Louiecris M. Regudon; Alberto D. Yazon; Karen A. Manaig; Sherwin B. Sapin; Victoria E. Tamban (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2022)
The traditional teaching method has been employed in the educational system for a long time and requires no active engagement from the students, making lessons challenging to comprehend. The use of gamification techniques in learning, on the other hand, removes the formalities of learning and allows learners to learn while having fun. This qualitative phenomenological study aimed to investigate the students' perspective on using gamification techniques in teaching and learning exploratory courses in Technology and Livelihood Education. The study explored the game experiences of 7 participants who experienced and were affected by using gamification techniques in education. This study used the Modified Stevick-Colaizzi-Keen phenomenological method of data analysis to examine the participants' transcripts. Analysis of the data gathered during the interviews developed four themes: 1) Connect Building relationships; 2) Change: Traditional schooling is too formal and Boring; 3) Captivate: Learning is fun when it is linked to memorable experience; 4) Compete: To compete and be recognized. Findings from the study recommended the following: a) educational institutions should consider including the use of gamification techniques in their curriculum to provide students with appropriate learning opportunities; b) researchers and developers can create more engaging resources for students' enjoyment and learning; c) school administrators should consider enrolling teachers in professional development seminars and training linked to gamification approaches; d) future scholars can choose to perform a qualitative and quantitative study on their subject areas to add to the body of knowledge in this understudied field, and e) future study collaborations on the application of gamification approach in teaching and learning can be done with educators from other countries. Keywords:   Gamification Techniques; Games; TLE; Exploratory Courses